Effect of Lasalocid on performance of grazing steers - Corah, L.R.; Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station, 2011)
Steers fed 200 mg of Lasalocid per day while grazing bromegrass pasture gained 7.6% faster than non-medicated controls; however, this difference was not statistically significant.
Keywords: Beef; Steer; Gain; Performance